A kind of inoculant for cast iron and preparation method of the inoculant
By using a specific synthetic process to produce cast iron inoculants, the shortcomings of existing inoculants in improving casting performance and uniformity are solved, and more efficient and uniform inoculant effects and lower energy consumption are achieved.
Patent Information
- Application Number
- CN202210601925.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-30
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-05-30
AI Technical Summary
The existing cast iron inoculant has shortcomings in improving the performance and uniformity of castings, and its production process makes it difficult to ensure the uniformity and consistency of product materials.
A special synthetic method is adopted to melt high-grade iron sulfide and rare earth ferrosilicon through an intermediate frequency furnace to form a granular ferrosilicon-based alloy incubator. The inoculant contains a specific proportion of elements such as silicon, calcium, rare earths, bismuth, etc. The silicon element part exists in the FeSi phase and the FeSi2 phase, the sulfur element exists in the rare earth sulfide, and the bismuth element exists in the intermetallic compound.
The incubation effect and uniformity of the incubator are significantly improved, the dissolution temperature and melting enthalpy are reduced, the rate of dissolution and absorption are increased, the risk of defects is reduced, and the casting performance is ultimately greatly improved.
Smart Images

Figure CN115216578B_ABST
Abstract
Description
Technical field:
[0001] The invention relates to the field of production, smelting and preparation technology of cast iron parts, and in particular to an inoculant for cast iron and a preparation method thereof, and a method for improving the performance and uniformity of cast iron parts by using the inoculant. Background technology:
[0002] The foundry industry is one of the country's basic industries, and its products involve military, civil, aerospace, railway, automobile, power equipment, infrastructure, and various industrial and agricultural machinery manufacturing. Castings are referred to as castings, which are divided into non-ferrous castings and ferrous castings. Ferrous castings are further divided into cast iron castings and steel castings.
[0003] Iron castings usually contain 2%-4% carbon. Most of the carbon in castings at room temperature appears in the form of graphite of different shapes. According to different graphite forms, iron castings are subdivided into ductile iron, gray iron, vermicular iron, etc. In the production process of iron castings, inoculants and inoculation processes are required to improve the existence form, distribution, size, and form of carbon in iron castings, thereby changing or improving the performance of iron castings. These properties include but are not limited to mechanical properties, cutting properties, natural frequency, aging properties, etc. The amount of inoculant added during the casting production process is usually 0.05-1% of the total mass of molten iron. The amount added is not large, but the role it plays is very critical.
[0004] In the production process of cast iron parts, through a certain inoculation process, adding appropriate inoculants can achieve the following purposes. 1. Effectively reduce the formation of casting chill (large Fe3C structure, usually referred to as carbide or chill in the industry), thereby improving and guaranteeing the mechanical properties of castings, reducing the hardness of castings, and improving machining performance. 2. Increase or adjust the amount of graphite precipitation, while improving the graphite morphology, reducing the shrinkage tendency during the casting molding process, and improving the material density, thereby increasing the product yield and further improving the performance; 3. Improve or adjust the casting matrix structure, usually the ratio of pearlite and ferrite, and then adjust the required performance of the casting in a targeted manner; 4. Improve the uniformity of the casting material, including the distribution of matrix structure and graphite. Usually due to the complex structure and different sizes of casting products, the uniformity and consistency of casting performance are also crucial.
[0005] The inoculant used in the cast iron industry is usually a ferrosilicon-based alloy. Among them: the silicon (Si) element content is generally 40%-80% by mass, which is usually considered to be a solvent element; it contains inoculant elements with different composition contents, such as Ca, Al, Ce, La, Ba, Sr, Zr, Bi, Sb, Mn, etc.; it contains impurities such as C, SiO2, ash, etc.; Fe is the balance. As an industrial additive used in batches, the quality standards of the inoculant that the market can pay attention to are only the composition range and particle size distribution of simple individual elements. Therefore, inoculant manufacturers simply match products according to the composition range and particle size distribution of individual elements. This is the current status of the industry. Only looking at the composition and not paying attention to the structure and composition is equivalent to the mobile phone, automobile and other industries only looking at the composition of parts, and the chip industry only looking at the chemical composition of the wafer.
[0006] Some companies, units or individuals have paid attention to the effect of adding different elements or compounds on the effect of inoculants, but they are only concerned about one thing and have not developed the comprehensive effects of inoculant solvent elements, inoculant elements, compound phases and structures. Patent WO99 / 29911 (CN1281513A) mentions that adding sulfides to an inoculant containing La / Ce and metal oxides can improve the production of graphite nodules in ductile iron. The oxides, sulfides and Ce-containing ferrosilicon alloys are all physically mixed, and there is no structural difference in the matrix alloy. Due to the effect of gravity, physically mixed materials must have segregation and aggregation. The longer the storage time, the more serious the segregation and aggregation of the materials will be. In addition, industrial products have to be transported and handled, so it is difficult to guarantee the uniformity and consistency of product materials. Patent WO2018 / 004356 (CN109477154A) discusses the effect of physically mixing bismuth oxide (Bi2O3), iron oxide (Fe2O3) and ferrous sulfide (FeS) in ferrosilicon alloy on the inoculation of castings. In the process of adding all oxides to the cast iron liquid, in addition to playing the role of inoculating or nucleating particles, they will also increase the slag tendency and form casting defects. Patent WO2014 / 147342 (CN105121061A) discusses the structure of an inoculant, including a supporting material and powdered particles coated on its surface, which is essentially a form of physical attachment. Summary of the invention:
[0007] The present invention designs and develops an inoculant for cast iron and a preparation method thereof. Through a special synthesis method, the inoculant can greatly improve the inoculation effect, improve the inoculation uniformity, reduce the temperature required for the inoculant to dissolve, reduce the melting enthalpy of the inoculant, increase the speed of the inoculant being dissolved and absorbed during use, and also reduce the risk of defects caused by the inoculant addition process. Ultimately, the performance of the casting itself can be greatly improved.
[0008] Description of the invention:
[0009] According to a first aspect, the present invention relates to an inoculant for cast iron, wherein the inoculant is a granular ferrosilicon-based alloy, the alloy comprising 40-80% by weight of silicon, 0.5-5% by weight of calcium, 0-5% by weight of rare earth (e.g., cerium and / or lanthanum), 0-5% by weight of bismuth, 0-5% by weight of aluminum, 0-5% by weight of barium, 0-5% by weight of sulfur, a total amount of impurities (including free carbon, ash and other oxides) not exceeding 2% by weight, and the remainder being iron.
[0010] The silicon element in the inoculant of the present invention exists in the form of a compound of silicon and iron, mainly including FeSi phase and FeSi2 phase; the other part of the silicon element exists in the form of elemental silicon;
[0011] The sulfur element in the inoculant of the present invention is mainly present in the form of rare earth sulfides, mainly cerium sulfide and / or lanthanum sulfide;
[0012] The bismuth element in the inoculant of the present invention is partially present in the form of an intermetallic compound with a rare earth element, mainly an intermetallic compound of bismuth and cerium and / or lanthanum;
[0013] Verification has found that the inoculant produced based on the above two points promotes the formation of more graphite nodules in ductile iron, inhibits the production of carbides in castings more effectively, and has a more stable inoculation effect than the inoculant with the same elemental composition but simply smelted.
[0014] The inoculant of the present invention is more completely fused with the matrix phase at room temperature, reacts continuously during melting and / or dissolving, has no interference from impurities, and requires lower energy consumption. The inoculant phase refers to a compound phase containing rare earth elements (e.g., cerium and / or lanthanum), bismuth, calcium, aluminum, barium, and sulfur; the matrix phase refers to a silicon single phase and a ferrosilicon compound phase (mainly including a FeSi phase and a FeSi2 phase);
[0015] According to a preferred embodiment, the various phases in the inoculant of the present invention are refined, including the matrix phase and the inoculant phase, forming various phase distributions similar to "grains". Compared with existing products on the market, the number of "grains" formed per unit area of the inoculant of the present invention is increased by at least one order of magnitude (some even two orders of magnitude), and the distribution of the phases is more dispersed and uniform, and is also distributed in layers at a size of 100μm, such as Figure 2 As shown in the figure, the thickness of the silicon single phase "grain" layer is 10-100 μm; the distribution of the nucleating element phase is similar to the distribution of flake graphite in gray cast iron, which is uniform and dispersed. Under 100 times magnification, at 1mm 2 Within the area, the number of "grains" containing the nucleus phase reaches more than 200.
[0016] Verification found that the inoculant produced according to the above two points has a faster melting / dissolving speed, lower energy consumption, less slag tendency and higher inoculation efficiency than similar ferrosilicon-based inoculants under the same casting conditions. Figure 6 As shown in Table 2. In other words, there are fewer restrictions when casting, the side effect of causing slag inclusion defects in castings is less likely to occur, and the amount of inoculant required to achieve the same casting inoculation requirements is lower.
[0017] The second aspect relates to a method for producing the cast iron inoculant of the present invention.
[0018] Step 1: Select high-grade iron sulfide and rare earth ferrosilicon as raw materials, mix them evenly according to a certain mass percentage, and place them in a medium frequency furnace to smelt to 1300-1350°C. The alloy in the furnace is a completely molten and uniform liquid alloy liquid, and the scum is scraped off at the same time. The alloy liquid is cast into a graphite ingot plate and naturally cooled to room temperature. The ingot thickness is 10-50mm, and then broken into pieces of 10-50mm in size to obtain an A series intermediate alloy. During the preparation process, the mass percentage of iron sulfide is in the range of 5-50%, and the mass percentage of rare earth ferrosilicon is in the range of 50-95%, and the sum of the two is 100%.
[0019] Step 2, select high-grade rare earth ferrosilicon and metal bismuth ingots as raw materials. First, place the rare earth ferrosilicon in a medium frequency furnace and smelt it to about 1300℃ (±20℃), which is a liquid metal liquid, and let it stand to remove the scum. Then add the metal bismuth ingot according to a certain mass percentage, heat it to 1350-1400℃, quickly cast it into a graphite ingot plate and cool it naturally to room temperature. The ingot thickness is 10-50mm, and then it is broken into pieces of 10-50mm in size to obtain a B-series intermediate alloy. During the preparation process, the mass percentage of the metal bismuth ingot is in the range of 10-50%, and the mass percentage of the rare earth ferrosilicon is in the range of 50-90%, and the sum of the two is 100%.
[0020] Step 3: Select high-grade ferrosilicon, ductile iron and silicon-barium alloy as raw materials, mix them evenly according to a certain mass percentage, and place them in a medium frequency furnace in the order of pig iron, silicon-barium alloy and ferrosilicon to smelt to 1300-1350°C. The alloy in the furnace is a completely molten and uniform liquid alloy, and the scum is removed at the same time. Add A series master alloy and / or B series master alloy according to a certain mass percentage, and quickly heat up by 30-100°C until the temperature of the molten metal in the furnace is around 1400°C (±20°C).
[0021] Step 4: Cooling, solidification, crushing and screening:
[0022] According to one implementation scheme, the ingot is quickly cast out of the furnace and naturally cooled to room temperature in a graphite ingot plate, the ingot thickness is 10-50 mm, and the ingot is crushed and sieved into granular inoculants of different particle sizes.
[0023] According to another embodiment, the alloy liquid is cooled to a solid state (below 900°C) by a rapid cooling device, with a cooling rate greater than 50°C / second, and then placed in a graphite container to cool naturally to room temperature. Finally, the alloy liquid is crushed and sieved into granular inoculants of different particle sizes. Description of the drawings:
[0024] Figure 1 The planar scanning electron microscope (SEM) metallographic image of the I2 inoculant of Comparative Example 2 is shown, using backscattered electron imaging, magnified 100 times;
[0025] Figure 2 The planar scanning electron microscope (SEM) metallographic image of the I8 inoculant of Example 4 is shown, using backscattered electron imaging, magnified 100 times;
[0026] Figure 3 The planar scanning electron microscope (SEM) metallographic image of the actual product particles of the I4 inoculant of Comparative Example 4 is shown, using a backscattered electron image, magnified 100 times;
[0027] Figure 4 The planar scanning electron microscope (SEM) metallographic image of the actual product particles of the I8 inoculant of Example 4 is shown, using a backscattered electron image, magnified 100 times;
[0028] Figure 5 The differential scanning calorimetry analysis result (DSC) of the I4 inoculant of Comparative Example 4 is shown;
[0029] Figure 6 The differential scanning calorimetry analysis result (DSC) of the I8 inoculant of Example 4 is shown; Specific implementation method:
[0030] Comparative Example
[0031] According to the existing technology, high-quality inoculants on the market are directly purchased as comparative examples, which are: Comparative Example 1, inoculant number I1, silicon-calcium inoculant, produced in Ningxia, China, main components: 72.8% Si, 1.53% Ca, 0.2-0.7mm; Comparative Example 2, inoculant number I2, silicon-barium inoculant, produced in Inner Mongolia, China, main components: 71.4% Si, 4.87% Ba, 1.54% Ca, 0.2-0.7mm; Comparative Example 3, inoculant number I3, silicon-rare earth inoculant, produced in Canada, main components: 74.7% Si, 1.9% Ce, 0.2-0.7mm; Comparative Example 4, inoculant number I4, silicon-bismuth inoculant, produced in France, main components: 71.2% Si, 0.85% Bi, 1.34% Ca, 0.2-0.7mm. The conditions of each inoculant are shown in Table 1.
[0032] contrast Origin Main chemical components of inoculant Master Alloy Cooling method serial number contrast Comparative Example 1 China 72.8%Si,1.53%Ca none Natural cooling <![CDATA[I1]]> Prior art Comparative Example 2 China 71.4%Si, 4.87%Ba, 1.54%Ca none Natural cooling <![CDATA[I2]]> Prior art Comparative Example 3 Canada 74.7%Si,1.9%Ce none Natural cooling <![CDATA[I3]]> Prior art Comparative Example 4 France 71.2%Si, 0.85%Bi, 1.34%Ca none Natural cooling <![CDATA[I4]]> Prior art Example 1 China 70.6%Si, 1.67%Ce, 0.36%S <![CDATA[A1]]> Natural cooling <![CDATA[I5]]> The present invention is related Example 2 China 70.3%Si, 1.17%Bi, 0.52%Ce <![CDATA[B1]]> Natural cooling <![CDATA[I6]]> The present invention is related Example 3 China 71%Si,1.2%Bi,0.87%Ce,0.1%S <![CDATA[A1+B1]]> Natural cooling <![CDATA[I7]]> The present invention is related Example 4 China 71.3%Si,1.3%Bi,0.91%Ce,0.1%S <![CDATA[A1+B1]]> High speed cooling <![CDATA[I8]]> The present invention is related
[0033] Example 1
[0034] Production of inoculants
[0035] High-grade iron sulfide (sulfur content ≥30%) and rare earth ferrosilicon (rare earth content ≥30%, wherein the mass ratio of cerium to lanthanum is 60:40 to 85:15) are selected as raw materials, and after uniformly mixing 15% of iron sulfide and 85% of rare earth ferrosilicon by mass, they are placed in a medium frequency furnace and smelted to 1300-1350°C at the same time. The alloy in the furnace is a completely molten and uniform liquid alloy liquid, and the scum is scraped off at the same time. The alloy liquid is cast into a graphite ingot plate and naturally cooled to room temperature. The ingot thickness is 10-50mm, and then broken into 10-50mm pieces to obtain A1 master alloy.
[0036] Select high-grade ferrosilicon (silicon content ≥ 72%) and ductile iron raw materials, mix them evenly according to a certain mass percentage, and place them in a medium frequency furnace in the order of pig iron, silicon-barium alloy, and ferrosilicon to smelt to 1300-1350℃. The alloy in the furnace is a completely molten and uniform liquid alloy, and the scum is removed at the same time. Add A1 master alloy according to 6% mass percentage, and quickly heat up 30-100℃ until the temperature of the molten metal in the furnace is around 1400℃ (±20℃).
[0037] It is quickly cast into a graphite ingot plate and naturally cooled to room temperature. The thickness of the ingot is 10-50 mm, and it is crushed and sieved into 0.2-0.7 mm granular inoculant I5. The measured composition is: 70.6% Si, 1.67% Ce, 0.36% S, and the specific information is shown in Table 1.
[0038] Example 2
[0039] Production of inoculants
[0040] Select high-grade bismuth ingots (bismuth content ≥ 99%) and rare earth ferrosilicon (rare earth content ≥ 30%, wherein the mass ratio of cerium to lanthanum is 60:40 to 85:15) as raw materials, and prepare bismuth ingots with a mass percentage of 30% and rare earth ferrosilicon with a mass percentage of 70%. First, smelt the rare earth ferrosilicon in a medium frequency furnace to about 1300°C (±20°C) to form a liquid metal liquid, and let it stand to remove the scum. Then add a metal bismuth ingot according to the total mass percentage of 30%, heat it to 1350-1400°C, quickly take it out of the furnace and cast it in a graphite ingot tray and cool it naturally to room temperature. The ingot thickness is 10-50mm, and then it is broken into pieces of 10-50mm in size to obtain a B1 intermediate alloy.
[0041] Select high-grade ferrosilicon (silicon content ≥ 72%) and ductile iron raw materials, mix them evenly according to a certain mass percentage, and place them in a medium frequency furnace in the order of pig iron, silicon-barium alloy, and ferrosilicon to smelt to 1300-1350℃. The alloy in the furnace is a completely molten and uniform liquid alloy, and the scum is removed at the same time. Add B1 master alloy according to 4% mass percentage, and quickly heat up 30-100℃ until the temperature of the molten metal in the furnace is around 1400℃ (±20℃).
[0042] It is quickly cast into a graphite ingot plate and naturally cooled to room temperature. The thickness of the ingot is 10-50 mm, and it is crushed and sieved into 0.2-0.7 mm granular inoculant I6. The measured composition is: 70.3% Si, 1.17% Bi, 0.52% Ce, and the specific information is shown in Table 1.
[0043] Example 3
[0044] Production of inoculants
[0045] The intermediate alloys A1 and B1 in Example 1 and Example 2 are used. High-grade ferrosilicon (silicon content ≥ 72%) and ductile iron raw materials are selected, uniformly mixed according to a certain mass percentage, and then placed in a medium frequency furnace in the order of pig iron, silicon-barium alloy, and ferrosilicon to be smelted to 1300-1350°C. The alloy in the furnace is a completely molten and uniform liquid alloy liquid, and the scum is scraped off at the same time. The intermediate alloys are added according to the mass percentages of 1.5% A1 and 4% B1, and the temperature is quickly raised by 30-100°C until the temperature of the molten metal in the furnace is about 1400°C (±20°C).
[0046] It is quickly cast into a graphite ingot plate and naturally cooled to room temperature. The ingot thickness is 10-50 mm, and it is crushed and sieved into 0.2-0.7 mm granular inoculant I7. The measured composition is: 71% Si, 1.2% Bi, 0.87% Ce, 0.1% S. The specific information is shown in Table 1.
[0047] Example 4
[0048] Production of inoculants
[0049] The intermediate alloys A1 and B1 in Example 1 and Example 2 are used. High-grade ferrosilicon (silicon content ≥ 72%) and ductile iron raw materials are selected, uniformly mixed according to a certain mass percentage, and then placed in a medium frequency furnace in the order of pig iron, silicon-barium alloy, and ferrosilicon to be smelted to 1300-1350°C. The alloy in the furnace is a completely molten and uniform liquid alloy liquid, and the scum is scraped off at the same time. The intermediate alloys are added according to the mass percentages of 1.5% A1 and 4% B1, and the temperature is quickly raised by 30-100°C until the temperature of the molten metal in the furnace is about 1400°C (±20°C).
[0050] The alloy liquid is cooled to a solid state (below 900°C) by a rapid cooling device, with a cooling rate greater than 50°C / second. Then it is placed in a graphite container and naturally cooled to room temperature, and finally crushed and sieved into 0.2-0.7mm granular inoculant I8. The measured composition: 71.3% Si, 1.3% Bi, 0.91% Ce, 0.1% S, the specific information is shown in Table 1.
[0051] Example 5
[0052] Inoculant Comparison 1
[0053] Large-particle alloys of I2 inoculants and I8 inoculants were selected, inlaid into metallographic test blocks, and an observation plane was ground out. The components of the phase were observed and compared using a scanning electron microscope (SEM), using the backscattered electron light source of the SEM, such as Figure 1 and Figure 2 As shown in the figure. The dark gray phase is the elemental silicon phase, the light gray phase is the iron-silicon compound phase, and the white (bright) phase is the inoculant element compound phase. The metallographic difference between the two inoculants can be clearly seen from the figure.
[0054] The various phase structures in the inoculant I8 prepared by the present invention are more refined, including the matrix phase and the inoculant phase, forming various phase distributions similar to "grains", which are also distributed in lamellar form at a size of 100μm, uniform and dispersed. The thickness of the silicon single phase "grain" lamellae is 10-100μm. The number of "grains" formed per unit area has increased by an order of magnitude. The distribution of the inoculant element phase is also more dispersed and more uniform, and the distribution is similar to the distribution of flake graphite in gray cast iron parts. Under a magnification of 100 times, at 1mm 2 Within the area, the number of "grains" containing the nucleus phase reaches more than 200.
[0055] Example 6
[0056] Inoculant Comparison 2
[0057] The actual finished particles of I4 inoculant and I8 inoculant were directly glued to the conductive glue on the sample stage. The SEM was used for observation and comparison. The backscattered electron light source of the SEM was used, such as Figure 3 and Figure 4As shown. As can be seen from the figure, as a comparative example, firstly, the two matrix phases on the I4 inoculant particles are basically separated, and the phase structure in the particles is relatively large, which is equivalent to particles of two different matrix phases mixed together. Secondly, the distribution segregation of the inoculant element phase in the I4 inoculant particles is serious, with inoculant elements on some particles but not on some particles. Moreover, the inoculant elements are concentrated together and unevenly distributed. In contrast, in the I8 inoculant particles prepared using our invention, each particle is a lamellar structure of two matrix phases, and the two matrix phases are completely blended together. In the I8 inoculant particles, the inoculant element phase is evenly distributed and dispersed. There are inoculant elements on each particle, and on each particle, the inoculant elements are also dispersedly distributed.
[0058] Example 7
[0059] Inoculant Comparison 3
[0060] The actual finished particles of I4 inoculant and I8 inoculant were selected, with a particle size range of 0.2-0.7 mm. The particles of the two inoculants were placed in a crucible, and the temperature was slowly raised from room temperature to 1450 degrees under argon gas, and differential scanning calorimetry (DSC) analysis was performed. The results are as follows Figure 5 and Figure 6 shown.
[0061] From the test results, there are many miscellaneous peaks in the I4 inoculant image, which means that the phases in the I4 inoculant are relatively complex and each phase reacts independently at high temperature. Figure 5 As shown. There are two main peaks in the figure, and the high-temperature phase and the low-temperature phase are separated independently, indicating that the two phases of the same material are melted separately under high temperature. Since the phase structure in the I4 inoculant is relatively large, in this case, the high-temperature phase and the low-temperature phase are melted independently during the actual melting of the I4 inoculant, and the overall melting / dissolving temperature depends on the high-temperature phase, which is greater than 1300°C, or even 1400°C. This will lead to a slow dissolution / melting speed of the I4 inoculant, which in turn increases the risk of slag defects in castings.
[0062] like Figure 6 As shown in the DSC test results of I8 inoculant, the peaks are relatively clean, and no impurity peaks are seen. This shows that the inoculant element phase and the matrix phase are fused together. In addition, the two main peaks are also fused together, indicating that the high-temperature phase and the low-temperature phase in the matrix phase are continuously melted as a whole, so the actual melting / dissolving temperature depends on the low-temperature phase, which is lower than 1300°C. Since the casting temperature of cast iron parts is generally 1300-1380°C, this greatly reduces the risk of slag formation (side effects) of the inoculant.
[0063] right Figure 5 and Figure 6By differentiating the middle curve, the actual phase change enthalpy of I4 inoculant and I8 inoculant can be obtained, as shown in Table 2. The phase change temperatures of I4 inoculant and I8 inoculant during the heating process are also listed in Table 2. It can be seen that the melting phase change enthalpy of I8 inoculant is much lower than that of I4 inoculant, and the energy consumption is reduced by 19%.
[0064] Product Comparison granularity First phase melting point Second phase melting point Melting enthalpy J / g Power consumption (kWh / ton) <![CDATA[I4]]> 0.2-0.7mm 1210.3 1328.3 352.8 98 <![CDATA[I8]]> 0.2-0.7mm 1207.8 - 285.8 79.39
[0065] Example 8
[0066] Inoculant Application
[0067] The inoculants of Examples 1 to 4 and the inoculants of Comparative Examples 1 to 4, a total of 8 inoculants (I1 to I8) were selected for practical application comparison tests to observe the changes in the number of graphite nodules. The test selected ductile iron castings and compared them with the actual production castings (brand QT450-10). Two standard cast test blocks of 5mm and 25mm were prepared in advance on the castings. The weight of molten iron was 1000Kg, and a total of 13 boxes were cast from the same package of molten iron. The 3rd box to the 10th box were selected, and I1 to I8 inoculants were used for final inoculanting, respectively. The particle size of the inoculants was 0.2-0.7mm, and the amount added was 0.15% of the weight of the molten iron. The other conditions of the test were the same. When the last three-mold (box) casting was cast, the final composition of the casting was tested by sampling, which was 3.67% C, 2.65% Si, 0.21% Mn, 0.03% P, 0.011% S, and 0.034% Mg. The measured results are shown in Table 3.
[0068] Table 3. Comparison of the application of inoculants on ductile iron
[0069]
[0070] From the test comparison results, the inoculant of the present invention has excellent inoculation performance on both 5 mm test blocks and 25 mm test blocks, which is better than the existing inoculants of the same type on the market, and promotes the production of more graphite balls with a higher spheroidization rate of graphite balls.
Claims
1. A method for producing an inoculant for cast iron, characterized in that: The inoculant contains 40-80% by weight of silicon, 0.5-5% by weight of calcium, 0-5% by weight of cerium and / or lanthanum, 0-5% by weight of bismuth, 0-5% by weight of aluminum, 0-5% by weight of barium, 0-5% by weight of sulfur, and a total amount of impurities not exceeding 2% by weight of the total weight, the remainder being iron; The production and preparation method of the inoculant comprises the following steps: Step 1, select high-grade iron sulfide and rare earth ferrosilicon as raw materials, mix them uniformly according to a certain mass percentage, and place them in a medium frequency furnace to smelt to 1300-1350° C. The alloy in the furnace is a completely molten and uniform liquid alloy liquid, and the scum is removed at the same time, and the alloy liquid is cast into a graphite ingot plate and naturally cooled to room temperature. The ingot thickness is 10-50 mm, and then broken into pieces of 10-50 mm in size to obtain an A series master alloy. During the preparation process, the mass percentage of iron sulfide is in the range of 5-50%, and the mass percentage of rare earth ferrosilicon is in the range of 50-95%, and the sum of the two is 100%; Step 2, select high-grade rare earth ferrosilicon and metal bismuth ingots as raw materials, first place the rare earth ferrosilicon in a medium frequency furnace and smelt it to 1300°C ± 20°C to form a liquid metal liquid, stand it and scrape off the scum, then add the metal bismuth ingot according to a certain mass percentage, heat it to 1350-1400°C, quickly take it out of the furnace and cast it in a graphite ingot plate and naturally cool it to room temperature, the ingot thickness is 10-50mm, and then it is broken into pieces of 10-50mm in size to obtain a B series master alloy. During the preparation process, the mass percentage of the metal bismuth ingot is in the range of 10-50%, and the mass percentage of the rare earth ferrosilicon is in the range of 50-90%, and the sum of the two is 100%; Step 3: Select high-grade ferrosilicon, ductile iron and silicon-barium alloy as raw materials, mix them uniformly according to a certain mass percentage, place them in a medium frequency furnace in the order of pig iron, silicon-barium alloy and ferrosilicon, and smelt them to 1300-1350° C. The alloy in the furnace is a completely molten and uniform liquid alloy, and at the same time, remove the scum, add A series master alloy and / or B series master alloy according to a certain mass percentage, and quickly heat up by 30-100° C. until the temperature of the molten metal in the furnace is 1400° C.±20° C.; Step 4, the final step is the cooling and solidification of the inoculant melt, and the crushing and screening of the finished product.
2. The method for producing a cast iron inoculant according to claim 1, characterized in that: The silicon and iron elements in the inoculant are matrix elements, wherein most of the silicon and iron elements exist in the form of silicon and iron compounds, mainly including FeSi phase and FeSi2 phase; another major component of the silicon element exists in the form of single silicon phase.
3. The method for producing a cast iron inoculant according to claim 1, characterized in that: The sulfur element in the inoculant mainly exists in the form of cerium sulfide and / or lanthanum sulfide.
4. The method for producing a cast iron inoculant according to claim 1, characterized in that: The bismuth element in the inoculant is partially present in the form of an intermetallic compound of bismuth and cerium and / or lanthanum; the other part of the bismuth element is present in the form of bismuth oxide.
5. The method for producing an inoculant for cast iron according to claim 1, characterized in that: In step 4, according to one implementation scheme, the ingot is quickly cast into a graphite ingot plate and naturally cooled to room temperature, the ingot thickness is 10-50 mm, and the inoculant is crushed and sieved into granular inoculants of different particle sizes.
6. The method for producing an inoculant for cast iron according to claim 1, characterized in that: In step 4, according to another implementation scheme, the alloy liquid is cooled to a solid state by a rapid cooling device at a cooling rate greater than 50°C / second, and then placed in a graphite container to naturally cool to room temperature, and finally crushed and sieved into granular inoculants of different particle sizes.
Citation Information
Patent Citations
Inoculant with surface particles
CN105121061A
Cast iron inoculant and method for production of cast iron inoculant
CN109477154A
Cast iron inoculant and method for production of cast iron inoculant
CN1281513A
Cast iron inoculant and method for production of cast iron inoculant
WO1999029911A1
Inoculant with surface particles
WO2014147342A1